Efficacy of Tripterygium wilfordii Hook F on animal model of Diabetic Kidney Diseases: A systematic review and meta-analysis. (5th December 2021) - Jin, Di; Yu, Miao; Li, Xiangyan; Wang, Xiuge
Abstract: Ethnopharmacological relevance: Tripterygium wilfordii Hook F (TwHF) has been clinically applied in the treatment of Diabetic Kidney Diseases (DKD). A large number of animal experiments focused on the TwHF treatment of DKD were conducted every year, but the evidence for these preclinical studies is unclear. Aim of the study: This study aims to evaluate the efficacy of TwHF on diabetic nephropathy through a stematic reviews and meta-analysis of animal models, and whether it has an effect on improving kidney pathology, renal function indicators and blood sugar levels, it also summarizes the use of TwHF for treatment the underlying mechanism of DKD. Materials and methods: We systematically searched studies from PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang database from inception to May 2020. Chinese studies from the list of Chinese Core Journals would be included. SYRCLE's risk of bias tool for animal studies was applied to assess the methodological quality of studies. A meta-analysis was performed by using RevMan 5.3. Results: Out of 429 records identified in the initial search, 32 studies were selected. The results indicated that, compared with control group, TwHF treatment improved 24 h urine protein (24 h-UP) level (SMD - 4.21, 95% CI - 5.38 to - 3.04, P < 0.001), serum creatinine (Scr) (MD – 14.97, 95% CI – 20.42 to – 9.53, P < 0.001), blood urea nitrogen (BUN) (MD - 4.07, 95% CI - 5.49 to - 2.66, P < 0.001), blood glucose (Glu) (MD - 2.40, 95% CI - 4.304 to - 0.49, P = 0.01), Triglyceride (TG) (MD - 1.57, 95% CI - 2.06 to - 1.08, P < 0.001), and Cholesterol (TC) (MD - 1.49, 95% CI - 2.23 to - 0.75 P < 0.001); and increased the level of albumin (Alb) (MD 3.40, 95% CI 1.69 to 5.11, P < 0.001) and weight (MD 30.89, 95% CI 24.35 to 37.42, P < 0.001). There were no statistical difference on Alanine aminotransferase (ALT) (MD 3.00, 95% CI – 7.80 to 13.81, P = 0.59) and Aspartate aminotransferase (AST) (MD 0.77, 95% CI -15.05 to 16.60, P = 0.92) after TwHF. Meta regression analysis showed that the DKD model induced by different methods (type I/II), the dose of Tripterygium wilfordii and the intervention time were not the reasons for the heterogeneity of 24 h-UP, Alb, Glu, Scr, and BUN ( p > 0.05 ). Conclusions: TwHF is an effective and safe to treat DKD, which can protect the kidneys through anti-inflammation, improving oxidative stress and podocyte damage, and inhibiting mesangial cell proliferation and extracellular matrix proliferation. Graphical abstract: Image 1